Os avanços do direito animal e a especificidade do Brasil: uma análise a partir de leis, jurisprudência e descobertas científicas. - Silveira, Kelly Cristiny Lima (2020)
In recent years, animal rights issues have moved from the margin to the centre of political and legal debate. This bibliographical research was carried out using the consultation of books, Brazilian and other states legislation, court decisions and legal journals. As for the objectives, it is exploratory, after investigation or framing given to animals by the Brazilian Legal System with answer to the main question: are animals considered things for Brazilian Law? Having said that, at first, concepts and sources of Animal Law are defined. Then, a tracking of the status of animals throughout history is performed, based on relevant events or thoughts. The narrative begins with the philosophy of Pythagoras, follows by Aristotle, Descartes; lists the contribution of Darwin and the contemporary animalist philosophers who inaugurate the divergences between the currents of animal rights; and, finally, reaches the current days, a time when scientific discoveries (and other factors) involving animals have driven a new vision of law with these beings. In the third stage of this research, the transformations of the status of animals implemented in Austria, Germany, Switzerland, France, New Zealand and Portugal are described. Finally, a parallel is made between those external legislative reforms and the main manifestations of Animal Law in Brazil, fruit, mainly, of the jurisprudential construction coming from theoretical arguments gathered from decisions of the Supremo Tribunal Federal and Superior Tribunal de Justiça. The jurisprudence of the Courts, among the various contributions, gives to each animal, individually and independent of its ecological function, dignity and intrinsic value, corollary qualities of its own existence, completely removing the idea of "animal-thing".